Effect of driver charge on wakefield characteristics in a plasma accelerator probed by femtosecond shadowgraphy. (1st August 2022) - Schöbel, Susanne; Pausch, Richard; Chang, Yen-Yu; Corde, Sébastien; Couperus Cabadağ, Jurjen; Debus, Alexander; Ding, Hao; Döpp, Andreas; Foerster, F Moritz; Gilljohann, Max; Haberstroh, Florian; Heinemann, Thomas; et al.
Abstract: We report on experimental investigations of plasma wave structures in a plasma wakefield acceleration (PWFA) stage which is driven by electron beams from a preceding laser plasma accelerator. Femtosecond optical probing is utilized to allow for direct visualization of the plasma dynamics inside the target. We compare two regimes in which the driver propagates either through an initially neutral gas, or a preformed plasma. In the first case, plasma waves are observed that quickly damp after a few oscillations and are located within a narrow plasma channel ionized by the driver, having about the same transverse size as the plasma wakefield cavities. In contrast, for the latter robust cavities are recorded sustained over many periods. Furthermore, here an elongation of the first cavity is measured, which becomes stronger with increasing driver beam charge. Since the cavity length is linked to the maximum accelerating field strength, this elongation implies an increased field strength. This observation is supported by 3D particle-in-cell simulations performed with PIConGPU. This work can be extended for the investigation of driver depletion by probing at different propagation distances inside the plasma, which is essential for the development of high energy efficiency PWFAs.